The Effect on Gastric Emptying of Telaprevir-Based Triple Therapy for Chronic Hepatitis C Patients - Arata Oyamada; Makoto Arai; Tomoaki Matumura; Kenichiro Okimoto; Shoko Minemura; Keiko Saito; Daisuke Maruoka; Tomoo Nakagawa; Tatsuo Kanda; Tatsuro Katsuno; Osamu Yokosuka (Archives of Clinical Gastroenterology - Peertechz Publications, 2015)
Aim: We evaluated food intake in telaprevir-based triple therapy (telaprevir, pegylated-interferon, and ribavirin) and its relation to Gastric Emptying (GE). Methods: 17 patients received telaprevir combined with pegylated interferon plus ribavirin. The GE study was carried out using the 13C-acetate breath test and GE time was expressed as the peak time of 13CO2 excretion (Tmax). Results:  The average food intake was 1,851 ± 91, 1,338 ± 537 and 1,453 ± 537 kcal at 0, 1, and 2 weeks after the start of treatment, respectively, showing a significant decrease compared to that before treatment (p < 0.01 and p <0.05, paired t-test). The averages of Tmax values at 0, 1, and 2 weeks after the start of treatment were 48.4 ± 14.3 min, 56.9 ± 18.4 min and 58.0 ± 19.9 min, respectively. There was a significant difference between baseline and 1 week after the start of treatment (p<0.05, paired t-test). Food intake (kcal) showed a good correlation with the decrease of Tmax values (minutes) (Pearson's correlation test, r = -0.49, p < 0.05).  Conclusions: Telaprevir-based triple therapy caused reduced food intake and worsened GE.